IDegLira Versus Alternative Intensification Strategies in Patients with Type 2 Diabetes Inadequately Controlled on Basal Insulin Therapy. Issue 4 (December 2015) - Freemantle, Nick; Mamdani, Muhammad; Vilsbøll, Tina; Kongsø, Jens; Kvist, Kajsa; Bain, Stephen
Abstract Introduction IDegLira is a once-daily combination of insulin degludec (IDeg) and liraglutide. Trials directly comparing IDegLira with alternative strategies for intensifying basal insulin are ongoing. While awaiting results, this analysis compared indirectly how different strategies affected glycated hemoglobin (HbA1c ) and other outcomes. Methods A pooled analysis of five completed Novo Nordisk randomized clinical trials in patients with type 2 diabetes inadequately controlled on basal insulin was used to compare indirectly IDegLira (N = 199) with: addition of liraglutide to basal insulin (N = 225) [glucagon-like peptide-1 receptor agonist (GLP-1RA) add-on strategy]; basal–bolus (BB) insulin [insulin glargine (IGlar) + insulin aspart] (N = 56); or up-titration of IGlar (N = 329). A supplementary analysis was performed with the BB arm including patients who received IGlar or IDeg as basal insulin in the relevant trial (N = 210). All trials had comparable inclusion/exclusion criteria and baseline characteristics. Individual patient-level data were analyzed using multivariable statistical models with potential baseline heterogeneity accounted for using explanatory variables. Results At end of study, differences between IDegLira and BB or up-titrated IGlar, respectively, were as follows: reduction in HbA1c −0.30%, 95% confidence interval (–0.58; −0.01) and −0.65% (−0.83; −0.47); change in body weight −6.89 kg (−7.92; −5.86) and −4.04 kg (−4.69; −3.40) all in favor of IDegLira. Confirmed hypoglycemia rate was 122.8 (90.7; 166.1), 1060.8 (680.2; 1654.4), and 286.1 (231.1; 354.1) events/100 patient-years for IDegLira, BB, and up-titrated IGlar, respectively. Odds ratios for achieving HbA1c <7.0%, <7.0% without hypoglycemia, and <7.0% without hypoglycemia and no weight gain were greater with IDegLira versus up-titrated IGlar. The supplementary analysis yielded similar results to the main analysis. Results with IDegLira were similar to those for the 'GLP-1RA add-on' arm. Conclusion These results suggest that IDegLira may be more effective, with lower hypoglycemia rates and less weight gain, than up-titrated basal insulin or BB in patients uncontrolled on basal insulin.